Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pemebelian Sepeda Motor Yamaha Nmax Pada Dealer Subur Plus Teluk Jambe - Muhamad Ritsa Faisal; Kosasih Kosasih (STIE AMKOP, 2023)
This study aims to explain the description of product quality, price, on purchasing decisions of Yamaha Nmax motorcycles at Subur Plus Dealer Teluk Jambe, as well as to examine the effect of product quality and price variables simultaneously and partially on purchasing decisions. This research was conducted using descriptive and verification methods, namely collecting, presenting, analyzing, and testing hypotheses, as well as making conclusions and suggestions.Samples were collected using the proportionate stratified random sampling method with a sample of 124 respondents from a population of 180 buyers. The data analysis techniques used were scale range analysis and path analysis with the help of Method of successive interval (MSI).From the results of the analysis of research data obtained several conclusions that the quality of the product 381 is in the criteria of moderately agree, the price of 436 is in the criteria of moderately agree, the purchase decision of 388 is in the criteria of moderately agree. There is a relationship between product quality and price of 0.481, this shows a fairly strong and unidirectional relationship because it has a positive value. There is a partial effect between product quality and purchasing decisions of 31.4% and there is a partial influence between price and purchasing decisions of 20.8%. There is a simultaneous influence between product quality and price on purchasing decisions for Yamaha Nmax motorcycles at Subur Plus Dealer Teluk Jambe by 52.2%, while the remaining 47.8% is the contribution of other variables not examined. Keywords: Product Quality_1, Price_2, Purchase Decisiom_3